A STUDY ON THE ASSESSMENT OF SAFETY OF A POLYHERBAL FORMULATION IN ACUTE DIARRHOEA - Santanu Munshi; *Ranjita Santra (Dhali); Manab Nandy; Swati Bhattacharya; Tapas Sur (International Journal of Ayurveda and Pharma Research, 2016)
Objective: To explore the safety profile of the proposed polyherbal formulation LQ 14 which is composed of various antimicrobial ingredients in rodents according to OECD (423) for acute oral toxicity study and OECD (407) for 28-days repeated dose toxicity study. Materials and methods: Acute toxicity studies and 28-days repeated dose toxicity were done on male Swiss slbino mice and Wistar albino rats. The animals were randomly divided into four groups of five animals each (n=20). In acute toxicity study, three doses of the extract (2.5-10 ml/kg body weights) were administered to 3 groups of the animals respectively. All animals were observed for 24 hours and general symptoms of toxicity and mortality were recorded. In 28-days repeated dose toxicity study, wistar male rats were grouped by randomized design and assigned to three groups of 6 animals each (n=18). Two doses of the extract (2.5, 5 ml/kg body weight) were administered daily to 2 groups. The last group was control in both and received 10, 5 ml/kg body weight of deionized water. Route of administration was oral in all the groups of animals. Results: No treatment related toxicity was found in both acute and repeated dose toxicity studies. Conclusion: The absence of biologically significant differences in the toxicological endpoints supports the safety of LQ14 in the treatment of diarrhea.